Polarity, Low Tone Spread, and Underspecification in the Kabiye Verb Phrase - David Roberts (LibraryPress@UF, 2021)
This autosegmental analysis of Kabiye verbal derivations and inflections demonstrates that tone patterns on adjectives and locative nominalizations are not the underlying forms of verb roots, as claimed by previous researchers, because they are in complementary distribution. Rather, verb roots are analyzed as being underlyingly /H, L/, and two additional morphological elements – verbal extensions and TAM prefixes – both reveal a ternary /H, -L, -∅/ contrast. In toneless extensions, this resolves an adjacency issue with regard to polarity of the TAM suffix, while the three floating tonal TAM prefixes either block, pre-empt or permit L tone spread from the subject pronoun onto the stem. The result is an integrated analysis of derivational and inflectional forms that dovetails with a previous analysis of the associative noun phrase.